PENGARUH PENDEKATAN PEMBELAJARAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI MOTIVASI BELAJAR SISWA KELAS IV SDN 100590 AIR KANAN - Camelia Dalimunthe, Putri; Sunardi; Puryati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low level of mathematical problem-solving ability among elementary school students and the suboptimal implementation of learning approaches that connect mathematical concepts with real-life situations. This study aims to examine the effect of the Indonesian Realistic Mathematics Education (PMRI) approach and learning motivation, as well as their interaction, on the mathematical problem-solving ability of fourth-grade students at SDN 100590 Air Kanan. The method used in this study is a quasi-experimental design with a treatment by level (2 × 2) design and a pretest–posttest nonequivalent control group design. This study employed a saturated sampling technique with a total sample of 40 students. Data collection techniques included essay tests to measure mathematical problem-solving ability and questionnaires to assess learning motivation, both of which had been tested for validity and reliability. Hypothesis testing was conducted through prerequisite tests, t-tests, two-way analysis of variance (ANOVA), and follow-up tests. The results showed that there is a significant effect of the PMRI approach on students' mathematical problem-solving ability. In addition, learning motivation also has a significant effect on this ability. Furthermore, there is an interaction between the PMRI learning approach and learning motivation on students' mathematical problem-solving ability. Further findings indicate that students with high motivation in PMRI learning achieved the highest performance, while students with low motivation still showed improvement compared to those taught using the expository approach.